PARTISIPASI ANGGARAN DAN KINERJA MANAJERIAL : GAYA KEPEMIMPINAN FIEDLER SEBAGAI VARIABEL MODERASI - Sherly Marsilia Sulaksono; Clara Susilawati (Jurnal Akuntansi Bisnis, 2012)
The study of the effect of budget participation on managerial performance has been much studied, one of which is Sumarno (2005). This study will improve Sumarnos research (2005) by using Fiedler's Leadership Style as a moderating variable. Fiedler Leadership style testified that leaders contribution to group performances effectivity depends on the way or the style of leadership (leadership style) and the suitability of the situation (the favourableness of the situation) that it faces. The sample in this study are the employees who participated in the preparation of the budget at hospitals in Semarang. The results showed that Fiedlers leadership style was unable to moderate the relationship between budgetary participation and managerial performance. The results of this analysis also obtained additional analysis which was stating that task-oriented leadership style may moderate the relationship between budgetary participation and managerial performance